Automated Driving Vehicles - Yi, Kyongsu; Song, Bongsob (CISM International Centre for Mechanical Sciences, Courses and Lectures, 2022)
This chapter introduces a full scope of autonomous vehicle technology ranging from perception to control. While a literature review for commercial environment sensors and sensor fusion to both model-based and data-driven approaches is summarized in Sect. 2, detailed decision and motion planning strategies for urban driving situations as well as highway are described. Moreover, some experimental results are demonstrated in Sect. 3. In Sects. 4 and 5, lateral and longitudinal control methods are proposed respectively in the hierarchical structure. The several upper controllers are designed to track the desired path and their performances are compared experimentally. The torque controller for a steering actuator as a lower controller is designed based on nonlinear control techniques. Similarly, the upper and lower controller for longitudinal control with consideration of human driver characteristics is proposed for better naturalistic driving performance. Finally, a scenario-based approach for validation of the autonomous vehicle technology including all proposed algorithms is investigated in the end.